Progressive Muscle Relaxation Techniques Reduces Anxiety in Fracture Recovery Patients at Haji Adam Malik General Hospital - Henrianto Karolus Siregar; Wanto Sinaga; Khairunnisa Batubara; Ivana Aprilia Pehopu; Fendy Yesayas (Media Keperawatan Indonesia, 2022)
Fracture is a disorder of the musculoskeletal system caused by damage to bone tissue. The progressive muscle relaxation technique is a deep muscle therapy that does not require imagination, persistence, and even suggestion that can be used by stretching and then relaxing the muscles. Progressive muscle relaxation techniques can help a person relax more when experiencing anxiety. The study aimed to identify the effect of progressive muscle relaxation techniques on anxiety in fracture recovery patients of research is a quantitative descriptive study with quasi-experimental research with a two-group pretest and post-test design approach. The treatment group was given a progressive muscle relaxation technique with as many as 15 movements starting from the facial muscles to the leg muscles for 20-40 minutes every day and carried out for 1 week. The results showed a positive effect of giving muscle progressive techniques to anxiety before and before intervention p-value = 0.000 (p <0.05). Based on the results of this study, it can be said that progressive muscle relaxation is effective in reducing anxiety scores of patients with fracture recovery.